Pelatihan Pembelajaran dan Penilaian Berbasis HOTS (Higher Order Thingking Skill) bagi guru SD - Effendi Effendi; Wahid Gunarto (Jurnal Indonesia Mengabdi, 2019)
The existence of the activities for teachers is based on the rapid development of technology and communication so as to also require changes in the pattern of learning and blowing related to the ability to think. Learning involving high-level thinking (HOTS) is indispensable in the era of the 4.0 industrial Revolution and the future because of the evolving science, relentless changes and tougher life competition. Therefore educators should strive for how students can be flexible in adapting to the changes. In the implementation of this activity use lecture methods, discussions and FAQs and practice. The material presented in its activities is material about the HOTS learning and assessment. After the activities carried out some of the benefits that are obtained namely: 1) In general participants who attended very enthusiastic about the material that delivered, 2) and feel the new knowledge related to learning and assessment of HOTS-based.